2007
DOI: 10.1161/atvbaha.107.144576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unfractionated Heparin and Glycoprotein IIb/IIIa Antagonists Versus Bivalirdin on Myeloperoxidase Release From Neutrophils

Abstract: Objectives-The objective of this study was to determine whether adjunctive therapy during percutaneous coronary intervention (PCI) affects markers of systemic inflammation or platelet activation. Despite different mechanisms of action, direct-thrombin inhibition with bivalirudin during PCI provided similar protection from periprocedural and chronic ischemic complications as compared with unfractionated heparin (UFH) plus planned use of GPIIb/IIIa antagonists in the REPLACE-2 and ACUITY trials. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
(37 reference statements)
1
23
0
1
Order By: Relevance
“…Some studies have in fact reported that UFH plus eptifibatide, but not bivalirudin, may cause neutrophil activation and mieloperoxidase release in patients undergoing percutaneous coronary intervention. 8 Further studies have shown that UFH promotes proinflammatory interactions between platelets and WBC, increasing platelet reactivity and favoring formation of platelet-leukocyte aggregates 9 and monocyte tissue factor expression. 10 In contrast, treatment with bivalirudin compared with UFH has been associated with attenuation of inflammation after elective percutaneous coronary intervention 11 or in animal models of cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have in fact reported that UFH plus eptifibatide, but not bivalirudin, may cause neutrophil activation and mieloperoxidase release in patients undergoing percutaneous coronary intervention. 8 Further studies have shown that UFH promotes proinflammatory interactions between platelets and WBC, increasing platelet reactivity and favoring formation of platelet-leukocyte aggregates 9 and monocyte tissue factor expression. 10 In contrast, treatment with bivalirudin compared with UFH has been associated with attenuation of inflammation after elective percutaneous coronary intervention 11 or in animal models of cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…20 We have only included patients on a prophylactic dosage of heparin regarding it as effective to avoid deep venous thrombosis. Furthermore, in our trial, we have observed 2 urogenital bleedings as adverse effects.…”
Section: Safety Of Tirofiban In Acute Strokementioning
confidence: 99%
“…Следует отметить, что риск развития кровоизлияния на фоне применения ингибиторов ГП IIb/IIIa повы-шается при их использовании в сочетании с анти-коагулянтами, например с гепарином [20]. В данное исследование включили только тех пациентов, кото-рым назначали гепарин в профилактической дозе в качестве препарата для предотвращения тромбоза глубоких вен.…”
Section: контроль качества данныхunclassified
“…37 Briefly, neutrophils were isolated from blood of adult human healthy donors and suspended in Hanks' balanced salt solution containing 0.25% BSA. Aliquots of neutrophils (2 ϫ 10 5 cells in 200 l) were loaded with 1 mol/L DHR123 (Molecular Probes) for 5 minutes at 37°C and then stimulated with rh-CD40L under defined conditions.…”
Section: Flow Cytometry Analysis Of Neutrophil Mac-1 Expression and Omentioning
confidence: 99%